2014
DOI: 10.3109/14764172.2014.957216
|View full text |Cite
|
Sign up to set email alerts
|

Histologic comparison of microscopic treatment zones induced by fractional lasers and radiofrequency

Abstract: This study provides the first comparison of MTZs induced by various fractional lasers and RF. These data provide basic information on proper laser and RF options. We think that these findings could be a good reference for information about fractional laser-assisted drug delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 18 publications
6
38
0
Order By: Relevance
“…For example, Sadick et al found a clear dose/effect relationship with maximum ablation depth of 200 μm and coagulation depth up to 300 μm. Shin et al showed maximum 118.43 μm ablation depth while using the highest power (100 W) which similar to depth found with Shallow program in our study.…”
Section: Discussionsupporting
confidence: 90%
“…For example, Sadick et al found a clear dose/effect relationship with maximum ablation depth of 200 μm and coagulation depth up to 300 μm. Shin et al showed maximum 118.43 μm ablation depth while using the highest power (100 W) which similar to depth found with Shallow program in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Previous histological studies revealed significant neoelastogenesis and neocollagenesis after fractional laser treatments with new dermal tissue replacing denaturated collagen within 10 week (Sadick & Rothaus, ). Researches also confirmed that erbium lasers resulted in low thermal damage than other fractional ablative lasers but usually produced more bleeding (Shin, Choi, Ahn, & Lee, ).…”
Section: Introductionmentioning
confidence: 84%
“…2. Several animal studies confirmed that the penetration depth of plasma on skin is 2-4 mm, depending on the energy settings [9,10]. Clinical observations also suggested that scars thicker than 4 mm often requires a higher energy setting and more treatment sessions.…”
Section: Discussionmentioning
confidence: 94%
“…With our research findings and relevant literature, we propose the following recommendations for treating scars: The findings show that FMRT was beneficial for treating scar thickness, color, and pliability but not for pain relief, itching, or scar contracture. Therefore, surgical correction is recommended for severely contracted scars prior to plasma treatment. Several animal studies confirmed that the penetration depth of plasma on skin is 2–4 mm, depending on the energy settings . Clinical observations also suggested that scars thicker than 4 mm often requires a higher energy setting and more treatment sessions.…”
Section: Discussionmentioning
confidence: 99%